Monotun: monopoli pantun sebagai media pembelajaran di kelas V sekolah dasar - Permatasari, Intan; Saputra, Erwin Rahayu; Alia, Dwi (IKIP Siliwangi, 2025)
Abstract This research aims to develop monotun media for learning to write rhymes in class V elementary school. With this research, we can find out the process of developing monotun media, determine the suitability of the media and user responses to monotun media, and find out the evaluation of monotun learning media on rhyme writing material in class V elementary school. This research isresearch and development (R&D) with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation.This research was carried out at SDN 5 Mekarsari, Banjar City involving class teachers and 46 class V students. Data collection techniques in this research were interviews, observation, questionnaires and documentation studies. The data analyzed is in the form of qualitative and quantitative data. Qualitative data was obtained from interviews, comments and suggestions from experts. Quantitative data was obtained from expert assessment scores and user questionnaires. The results of the expert validation test get an average value 89.1% category is very good or very suitable for use. Then the response from users in the first trial from a teacher got a percentage of 100% and the assessment from 22 students got an average score of 99.64%. In the second trial, two teachers got a percentage of 100% and the assessment of 46 students got an average score of 96.81%. It can be concluded that monotunal media in learning to write rhymes is suitable for use in learning. Keywords: Media, Writing, Poem.